1999
DOI: 10.1046/j.1439-0434.1999.147005265.x
|View full text |Cite
|
Sign up to set email alerts
|

The Partial Characterization of a Badnavirus Infecting the Greater Asiatic or Water Yam (Dioscorea alata)

Abstract: A bacilliform virus from Dioscorea alata, designated Dioscorea alata bacilliform virus (DaBV), from Barbados and West Africa and from other Dioscorea spp. from West African, Carribean, Asian and South American countries, has been characterized. The virus was transmitted by the mealybug, Planococcus citri and by mechanical transmission of partially purified preparations to several Dioscorea spp. DaBV was serologically related to a distinct bacilliform virus from Dioscorea bulbifera, to one isolate of sugarcane … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
28
0
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 23 publications
0
28
0
2
Order By: Relevance
“…Although YMV has been implicated as the most prevalent of all the viruses infecting yams (Thouvenel and Dumont, 1988, 1990; Goudou‐Urbino, 1995), others such as DAV, CMV and DaBV have also been identified as inducing conspicuous symptoms in Dioscorea spp. (Hughes et al., 1997; Odu et al., 1999; Phillips et al., 1999). It has been established that YMV infection causes significant reduction in plant vigour and subsequent tuber size (Craig, 1964; Thouvenel and Dumont, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…Although YMV has been implicated as the most prevalent of all the viruses infecting yams (Thouvenel and Dumont, 1988, 1990; Goudou‐Urbino, 1995), others such as DAV, CMV and DaBV have also been identified as inducing conspicuous symptoms in Dioscorea spp. (Hughes et al., 1997; Odu et al., 1999; Phillips et al., 1999). It has been established that YMV infection causes significant reduction in plant vigour and subsequent tuber size (Craig, 1964; Thouvenel and Dumont, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…germplasm in the 1970s (Harrison and Roberts, 1973), several hundred partial badnavirus reverse transcriptase (RT)-ribonuclease H (RNaseH) sequences have been characterised (Kenyon et al, 2008;Bousalem et al, 2009), but only a few complete Dioscorea bacilliform virus (DBV) genome sequences have been reported (Phillips et al, 1999;Seal and Muller, 2007;Bömer et al, 2016 andSukal et al, 2017;Umber et al, 2017). We have optimised a workflow involving total nucleic acid extractions and rolling circle amplification (RCA) combined with restriction enzyme analysis for the detection and amplification of DBVs present in yam germplasm.…”
mentioning
confidence: 99%
“…Badnavirus particles were first reported in yam in association with a flexuous virus, causing internal brown spot disease in D. alata and D. cayenensis in the Caribbean (Harrison and Roberts, 1973;Mantell and Haque, 1978). Two decades later yam badnaviruses were characterised by their nucleic acid and serological properties; particles isolated from D. alata and D. bulbifera were partially characterised and named informally as Dioscorea alata bacilliform virus (DaBV) and Dioscorea bulbifera bacilliform virus (DbBV) Phillips et al, 1999). These viruses were reported to induce leaf distortions and veinal chlorosis , although others found that often infected plants show no marked symptoms (Kenyon et al, 2008;Seal and Muller, 2007).…”
mentioning
confidence: 99%